2001
DOI: 10.1002/tea.1020
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive investigation of the science‐related career decisions of three African‐American college students

Abstract: Reports published since 1977 indicate that African Americans are underrepresented among Ph.D.‐holding scientists. Although researchers have identified numerous factors that correlate with career choice, they have failed to address students' reasons for choosing or not choosing science and science‐related careers. This study examines the career decisions of three African‐American college students. All three students began college aspiring toward science‐related careers. However, by the end of data collection on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…The item content is conceptually based in Pascarella and Terenzini’s (1980) model of college attrition. These subscales have been used widely in the student development and college persistence literature and recently adapted to measure perceived campus climate with African American STEM students (Brown et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The item content is conceptually based in Pascarella and Terenzini’s (1980) model of college attrition. These subscales have been used widely in the student development and college persistence literature and recently adapted to measure perceived campus climate with African American STEM students (Brown et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Next, students were asked to indicate which sources of career information were helpful for their career search from a 14 item predetermined list (Table 4). These career goals and values have also been noted to influence recruitment (Dowell 1996;Lewis and Collins 2001;Zhou et al 2004) and/or to influence interest in genetic counseling (Lega et al 2005). (Check all that apply)."…”
Section: Career Decisionsmentioning
confidence: 99%
“…In view of this, the important goal of relevant science education is to recognize the perceived need to prepare and equip learners for future occupation. Some studies revealed that some factors are taken into consideration by students when decisions on the career choice or path are made (Sadler et al 2012;Correl 2004;Lewis and Collins 2001). Such factors are likely to be the different hopes and priorities students hold for their future, which might be important for the choice of a future occupation or job.…”
Section: Literature Reviewmentioning
confidence: 99%